2021
DOI: 10.1007/s41468-021-00072-4
|View full text |Cite
|
Sign up to set email alerts
|

Improved approximate rips filtrations with shifted integer lattices and cubical complexes

Abstract: Rips complexes are important structures for analyzing topological features of metric spaces. Unfortunately, generating these complexes is expensive because of a combinatorial explosion in the complex size. For n points in $$\mathbb {R}^d$$ R d , we present a scheme to construct a 2-approximation of the filtration of the Rips complex in the $$L_\infty $$ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…An earlier version of this paper appeared at the 25th European Symposium on Algorithms [9]. In that version, we achieved a 3 √ 2-approximation of the L ∞ Rips filtration and correspondingly, a 3 √ 2d 0.25 -approximation of the L 2 case.…”
Section: Updates From the Conference Versionmentioning
confidence: 79%
See 1 more Smart Citation
“…An earlier version of this paper appeared at the 25th European Symposium on Algorithms [9]. In that version, we achieved a 3 √ 2-approximation of the L ∞ Rips filtration and correspondingly, a 3 √ 2d 0.25 -approximation of the L 2 case.…”
Section: Updates From the Conference Versionmentioning
confidence: 79%
“…In that version, we achieved a 3 √ 2-approximation of the L ∞ Rips filtration and correspondingly, a 3 √ 2d 0.25 -approximation of the L 2 case. In this version, we improve the weak interleaving of [9] to a strong interleaving to get improved approximation factors. We expand upon the details of scale balancing, among other proofs that were missing from the conference version.…”
Section: Updates From the Conference Versionmentioning
confidence: 99%
“…The improvement in size stems from the fact that at most (d + 1)-permutahedra can intersect in d dimensions which upper bounds the number of simplices in the nerve. The approximation quality has been improved to O( 4 √ d) in subsequent work, with size n2 O(d log k) [14]. In [15], it is also shown that, for any ε < 1/ log 1+c n with c ∈ (0, 1), any ε-approximate filtration must have a size of at least n Ω(log log n) .…”
Section: Introductionmentioning
confidence: 94%
“…, improving all previous results for the Euclidean case. We achieve this approximation based on the techniques devised in [14,15]. On a fixed scale α, we tile the space with a cubical grid, carefully select a subset of them and take their nerve as our approximation complex.…”
Section: Introductionmentioning
confidence: 99%
“…This problem is solved using persistent homology [12], [19], and simplicial homology is traditionally used. To solve similar problems, when calculating persistent homology in a metric space, [14] used cubical homology. Calculation algorithms are more efficient than algorithms based on triangulation methods, and they can naturally be used for sets of points in an n-dimensional space with the distance between points calculated using the L ∞ norm.…”
Section: Brief History and Applications Of Cubical Homologymentioning
confidence: 99%